2012
DOI: 10.1002/jsfa.5861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of saline stress on mineral composition, phenolic acids and flavonoids in leaves of artichoke and cardoon genotypes grown in floating system

Abstract: The results showed that the floating system could be considered an effective tool to improve quality aspects through proper management of the salt concentration in the nutrient solution. They also suggest that specific cultivars should be selected to obtain the desired profile of bioactive compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
87
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 46 publications
14
87
1
7
Order By: Relevance
“…4c and d). Similar to other medicinal plants (Abrol et al, 2012;Colla et al, 2013;Ksouri et al, 2007;Shao et al, 2015), moderate saline stress was more beneficial to the accumulation of bioactive compounds in the leaves of honeysuckle ( Fig. 4c and d), as severe stress greatly reduced carbon supply for phenolic synthesis by inhibiting CO 2 assimilation.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…4c and d). Similar to other medicinal plants (Abrol et al, 2012;Colla et al, 2013;Ksouri et al, 2007;Shao et al, 2015), moderate saline stress was more beneficial to the accumulation of bioactive compounds in the leaves of honeysuckle ( Fig. 4c and d), as severe stress greatly reduced carbon supply for phenolic synthesis by inhibiting CO 2 assimilation.…”
Section: Discussionsupporting
confidence: 54%
“…After 80 min incubation at room temperature in the dark, the absorbance at 760 nm was measured. Total phenolics content was determined by using a standard curve plotted with known concentrations of gallic acid (Colla et al, 2013). Flavonoid content was measured by using differential spectrophotometry method with ZrOCl 2 $8H 2 O for avoiding the disturbance of chlorogenic acid (Zhou et al, 2007).…”
Section: Measurements Of Phenolic Concentration and Dpph Scavenging Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Other cultivation features such as high salinity of nutrient solution (up to 4.8 mS cm -1 ), plant density and growing season could also affect yield and quality (nitrates, chlorophylls, vitamin C, carbohydrates and minerals content) of radish (Raphanus sativus), lamb's lettuce or corn salad (Valerianella locusta), rocket (Eruca sativa), artichoke (Cynara scolymus), cardoon (Cynara cardunculus), spiny chicory (Cichorium spinosum), and lettuce (Lactuca sativa) plants (Salerno et al, 2005;Fallovo et al, 2009a,b;Fontana and Nicola, 2009;Scuderi et al, 2009;Zanin et al, 2011;Colla et al 2012;Klados and Tzortzakis, 2014). Default et al (2006) reported that cultivation season affected significantly the growth rate and yield of six Cos type lettuce cultivars.…”
Section: Data Collectionmentioning
confidence: 99%